Effectiveness of Schema Therapy on Emotional Expression and Emotional Maturity of Conflicting Couples - Ahangari, Amir; Jahangir, Pantea; Dokaneifard, Farideh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Differences between couples and their continuous interaction can create multiple grounds for conflict, which may lead to severe negative outcomes such as stress, depression, grief, worry, and despair. The current research aimed to determine the effectiveness of schema therapy on emotional expression and emotional maturity in conflicting couples. Methods and Materials: The research method was a quasi-experimental design with pre-test, post-test, and a control group with a three-month follow-up period. The statistical population of the current study included all conflicting couples seeking help at counseling clinics and psychological services in District 1 of Tehran in 2023, from which 30 couples were selected through convenience sampling and randomly placed into two groups, 15 couples in the experimental group and 15 in the control group. Assessment tools included the Sanaie Marital Conflict Questionnaire (2000), the Singh and Bhargava Emotional Maturity Scale (1990), and the King and Emmons Emotional Expression Questionnaire (1990). The experimental group underwent eight two-hour schema therapy sessions based on Young et al. (2003) twice a week. Data were analyzed using repeated measures analysis of variance. Findings: Results showed significant differences between groups in post-test and follow-up in emotional expression and emotional maturity (p < .05), and schema therapy had lasting effects during the follow-up period (p < .05). Conclusion: Schema therapy can be used as an effective approach to improve emotional expression and emotional maturity in conflicting couples.